DEVELOPMENT OF GENDER-ORIENTED BUDGETING IN UKRAINE BASED ON THE EXPERIENCE OF FOREIGN COUNTRIES - Устинова, Ірина Петрівна; Ткаченко, Євгенія Миколаївна; Ліхітченко, Ірина Геннадіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: the article reveals the concept of gender budgeting, analyzes the experience of introducing and developing the concept of gender-oriented budgeting abroad. The attention is focused on the development results and effectiveness of the strategy of gender-oriented budgeting in Ukraine. Methods: general scientific and special legal methods were used in the work. Results: it is determined that Ukraine, in pursuit of effective and dynamic economic development, has an important task to achieve gender equality in society, and for this it is necessary to take into account gender in the budget. As the causes of the economic and social problems of protecting the rights of women and men differ, the costs of the state budget associated with their solution must meet the needs of both women and men. Gender budgeting is one of the effective methods to achieve the above goal, because such budgeting involves the rational structuring of revenues and expenditures from the state budget so that the needs of women and men are addressed proportionally. It is argued that the experience of many European countries is useful in implementing a gender budgeting strategy for Ukraine. Due to the implementation of such an effective gender policy instrument in Ukraine, the quality of financial management at the state and local levels will significantly improve, the economic situation in the country will improve, the system of financial resources allocation at all levels will improve, gender equality goals will be encouraged. accountability and public participation in the planning and distribution of the country’s budget. It is determined that today in Ukraine there are insignificant regulatory frameworks for the creation and implementation of gender-oriented policy, which would fully regulate all its stages, methods and means of implementation. Gender budgeting activities in Ukraine should include activities such as research, monitoring, study and development of implementation policies and strategies, and an information campaign. Only in the case of comprehensive regulation of the implementation process, including legislative, the result of the introduction of gender budgeting will have a positive impact on the state of the Ukrainian economy and society. The current experience of foreign countries is important for the formation of a new legislative field in Ukraine in the field of gender-oriented budgeting in order to further develop democratic processes in society and in public administration.